2018
DOI: 10.1021/acs.jafc.8b05422
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics and Metabolism of 3-Monochloropropane 1,2-Diol Dipalmitate in Sprague Dawley Rats

Abstract: Fatty acid esters of 3-monochloropropane 1,2-diol (3-MCPD) are a group of processing-induced toxicants. To better clarify their possible toxicological effects and mechanisms, it is important to investigate their absorption, distribution, metabolism, and excretion. In this study, the kinetic parameters of 3-MCPD dipalmitate in Sprague Dawley (SD) rat plasma were determined using ultraperformance liquid chromatography–triple quadrupole mass spectrometry. 3-MCPD dipalmitate was absorbed in rats with a C max of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…To study the effects of 3‐MCPD‐induced cytotoxicity, the experiments were investigated in the framework of the following three different in vitro models: isolated mitochondria from liver and kidney of Wistar rats, HEK‐293 cell line, and liver and kidney cells isolated from rats. Doses or concentrations of 3‐MCPD were selected based on the wide range of 3‐MCPD on HEK cell line as well as the previously published works (Abraham et al., 2013; Huang et al., 2018; Peng et al., 2016). All the doses used in this study exceeded the amounts to which humans are exposed, even more than what is taken through the real diet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the effects of 3‐MCPD‐induced cytotoxicity, the experiments were investigated in the framework of the following three different in vitro models: isolated mitochondria from liver and kidney of Wistar rats, HEK‐293 cell line, and liver and kidney cells isolated from rats. Doses or concentrations of 3‐MCPD were selected based on the wide range of 3‐MCPD on HEK cell line as well as the previously published works (Abraham et al., 2013; Huang et al., 2018; Peng et al., 2016). All the doses used in this study exceeded the amounts to which humans are exposed, even more than what is taken through the real diet.…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondrial isolation process was completely performed at 4 °C in 2 to 3 hr in order to guarantee high‐quality fresh mitochondria needed for determining the release of glutathione (GSH), ferric reducing–antioxidant power (FRAP), malondialdehyde (MDA), and cytochrome c. Fresh isolated mitochondria was incubated in Tris buffer solution for 1 hr at pH 7.4. The concentrations of 3‐MCPD were selected on the basis of either the authors’ pilot dose–response study (data not shown) or previous studies (Cho et al., 2008; Huang et al., 2018; Peng et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…[ 29 ] Kidney is the most sensitive target of 3‐MCPD exposure. [ 13,30 ] However, far too little data exist concerning the protective effect of DIO, a naturally secondary metabolite of plant, on renal injury induced by 3‐MCPD. In the current study, we aimed at evaluating the protective effect of DIO on kidney injury induced by 3‐MCPD in terms of ER stress, mitochondrial oxidative phosphorylation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, caerulein was shown to trigger cell necrosis by inhibition of the Wnt / β-Catenin pathway and lead to increased inflammatory cytokines. In-vivo studies showed that caerulein injection causes edema, inflammation and necrosis in pancreatic acinar cells [13,14].…”
Section: Discussionmentioning
confidence: 99%